Prevalence of Thyroid Diseases in an Occupationally Radiation Exposed Group: A Cross-Sectional Study in a University Hospital of Southern Italy - Vimercati, Luigi; De Maria, Luigi; Mansi, Francesca; Caputi, Antonio; Ferri, Giovanni M.; Luisi, Vito; Lovreglio, Piero; Cannone, Enza S.S.; Lorusso, Pietro; Gatti, Maria F.; Massagli, Chiara R.S.; Triggiani, Vincenzo (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background: Thyroid diseases occur more frequently in people exposed to ionizing radiation, but the relationship between occupational exposure to ionizing radiation and thyroid pathologies still remains unclear. Objective: To evaluate the prevalence of thyroid diseases in healthcare workers exposed to low-level ionizing radiation compared with a control group working at the University Hospital of Bari, Southern Italy, and living in the same geographical area, characterized by mild iodine deficiency. Methods: We ran a cross-sectional study to investigate whether healthcare workers exposed to ionizing radiation had a higher prevalence of thyroid diseases. Four hundred and forty-four exposed healthcare workers (241 more exposed, or “A Category”, and 203 less exposed, or “B Category”) and 614 nonexposed healthcare workers were enrolled during a routine examination at the Occupational Health Unit. They were asked to fill in an anamnestic questionnaire and undergo a physical examination, serum determination of fT3, fT4 and TSH, anti-TPO ab and anti-TG ab and ultrasound neck scan. Thyroid nodules were submitted to fine needle aspiration biopsy when indicated. Results: The prevalence of thyroid diseases was statistically higher in the exposed workers compared to controls (40% vs 29%, adPR 1.65; IC95% 1.34-2.07). In particular, the thyroid nodularity prevalence in the exposed group was approximately twice as high as that in the controls (29% vs 13%; adPR 2.83; IC95% 2.12-3.8). No statistically significant association was found between exposure to ionizing radiation and other thyroid diseases. Conclusion: In our study, mild ionizing radiation-exposed healthcare workers had a statistically higher prevalence of thyroid diseases than the control group. The results are likely due to a closer and more meticulous health surveillance programme carried out in the ionising radiation-exposed workers, allowing them to identify thyroid alterations earlier than non-exposed health staff.
Keywords: occupational exposure